Membangun Aplikasi Penyuluhan Usaha Mandiri Berbasis Android - Yuza Reswan; Pahrizal Pahrizal; Ujang Juhardi; Lambardo Adesio (UNIVED Press, 2024)
Indonesia is the most populous country in Southeast Asia and a great asset for the development of the Indonesian nation. A large population, if not managed properly, can pose problems in the future. The significant number of unemployed individuals in Indonesia creates its own challenges. The workforce in Indonesia still consists of a significant portion with primary and secondary education, while those with tertiary education are relatively few. The workforce can become the spearhead by creating job opportunities (job creators), so reducing unemployment cannot solely rely on job creation through private or foreign investment and the government. The tough competition among the increasing number of unemployed individuals each year has led to a new option, namely starting a self-employed business, which falls under the category of micro, small, and medium enterprises (MSMEs). MSMEs play a crucial role in improving and growing the community's economy. MSMEs are considered capable of withstanding any situation to achieve the welfare of the society. Establishing a new MSME is a challenging decision for those with limited funds, and careful consideration is required before starting one. The abundance of business options that can serve as references does not always guarantee success since not all businesses will thrive. Before deciding on the type of self-employment to pursue, prospective entrepreneurs must conduct research first. Therefore, there is a need for education and guidance for prospective entrepreneurs to avoid missteps when starting an MSME. The current technological advancements can be utilized to assist prospective entrepreneurs in providing relevant data related to self-employment, one of which is through the use of smartphone technology. Users can access literature regarding the process of establishing a self-employed business and learn from the experiences shared by entrepreneurs who are currently building their businesses